Exploring a digital collection of Neo-latin literature - Jovanović, Neven, filolog (2012)
At the moment, more neo-Latin texts are freely accessible than ever before; it is enough to remind oneself of the impressive Analytic Bibliography of On-Line Neo-Latin Texts, compiled by Dana F. Sutton; his bibliography, as of October 24, 2012, records 43,340 neo-Latin works on the internet. The time has come for neo-Latin scholars to face the question: what should we do with all these texts?
The problem is not only that no human being can read all that, nor that it is quite hard to discover among these thousands of titles ones
that we should read, nor that it is equally hard (once we’ve decided what we want) to discover a reliable “manifestation” of the text we want. The real problem is that, if we study these texts as we usually do — that is, focusing upon very carefully read key passages — we are using the internet simply as a vast library, and digital manifestations of texts as books. The main hypothesis of digital humanities, however, is that digital medium can change the way we understand and interpret languages, literature, history, philosophy, religion, arts.
We will try to demonstrate such qualitatively different digital approach to a collection of neo-Latin texts. The approach will combine (very
simple) computational experimentation on mass clusters of textual data with philological reading of passages brought to us from this experimentation by the computer, an assistant that’s better than us at some tasks but can’t perform others.
In this way we will explore texts by Janus Pannonius currently included in the digital collection Croatiae auctores Latini (CroALa, www.ffzg.unizg.hr/klafil/croala). The collection, currently containing 4.7 million words in 373 documents written by authors of Croatian origin (or connected with Croatia) from 976 to 1984, aims to make Croatian neo-Latin not only accessible, but also available for experiments of all kinds.
Keywords: CROALA; Croatiae auctores Latini; Digital library